2017
DOI: 10.1038/ismej.2017.184
|View full text |Cite
|
Sign up to set email alerts
|

Build your own soil: exploring microfluidics to create microbial habitat structures

Abstract: Soil is likely the most complex ecosystem on earth. Despite the global importance and extraordinary diversity of soils, they have been notoriously challenging to study. We show how pioneering microfluidic techniques provide new ways of studying soil microbial ecology by allowing simulation and manipulation of chemical conditions and physical structures at the microscale in soil model habitats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 31 publications
1
137
0
Order By: Relevance
“…A particular challenge will also be to include the smallest spatial scales (< cm), where patchy distribution patterns of bacteria are found (Franklin and Mills, ; Cordero and Datta, ; O'Brien et al ., ; Cordero and Stocker, ). Here, small scale‐sampling devices and microsensors and innovative experimental set‐up such as microofluid devices (see, e.g., Cordero and Datta, and references therein; Aleklett et al ., ) offer promising ways ahead. In summary, we suggest that more studies should be designed to test the predictions in the conceptual model presented in Fig.…”
Section: Factors Influencing the Importance Of Different Community Asmentioning
confidence: 99%
“…A particular challenge will also be to include the smallest spatial scales (< cm), where patchy distribution patterns of bacteria are found (Franklin and Mills, ; Cordero and Datta, ; O'Brien et al ., ; Cordero and Stocker, ). Here, small scale‐sampling devices and microsensors and innovative experimental set‐up such as microofluid devices (see, e.g., Cordero and Datta, and references therein; Aleklett et al ., ) offer promising ways ahead. In summary, we suggest that more studies should be designed to test the predictions in the conceptual model presented in Fig.…”
Section: Factors Influencing the Importance Of Different Community Asmentioning
confidence: 99%
“…Soil is one of the most complex habitats for life on Earth (Young & Crawford, 2004;Aleklett et al, 2018). It represents a highly compact form of three-dimensionally structured habitat featuring fine-scale gradients in physico-chemical characteristics, resource availability, and gas concentrations (Young & Crawford, 2004;Bardgett, 2005).…”
Section: Soil As a Complex Habitatmentioning
confidence: 99%
“…Future studies using newer technologies (e.g. molecular techniques and visual tracking techniques) to measure movement of soil animals may help to quantify constraints on the movement of soil organisms that affect the relative importance of niche-and neutral-based processes at the microsite scale (Nunan et al, 2003;Aleklett et al, 2018). Hovatter et al (2011) showed that dispersal limitation (independent of soil environmental factors) in soil bacterial communities (i.e.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Organizers and invited speakers highlighted ways to manipulate mycorrhizal fungal abundances in the field using fungicides and ingrowth cores (Ylva Lekberg), as well as the potential use of mutants (Thomas Irving), radioactive isotopes (Katie Field), enzymes (Bj€ orn Lindahl), and quantum dots (Victor Caldas), to study mycorrhizal function, nutrient transformation, uptake and movement. Thorunn Helgason outlined the potential use of genomic approaches, and Edith Hammer described a new technology that mimics the complexity of soils to increase realism in laboratory studies (Aleklett et al, 2018). Finally, Gaby Deckmyn reminded us all that in order to make full use of modeling, we need to collect more and better metadata (particularly environmental) during our surveys and experiments (Deckmyn et al, 2014).…”
Section: The Utility Of Existing and Emerging Technologiesmentioning
confidence: 99%